Salt reducing and saltiness perception enhancing strategy for shiitake (Lentinus edodes) bud using novel combined treatment of yeast extract and radio frequency. (15th February 2023) - Zhang, Lihui; Zhang, Min; Adhikari, Benu; Zhang, Lujun
Highlights: Yeast extract and RF decreased the addition of salt, and improved saltiness perception. Yeast extract and RF enhanced the antioxidant activity of samples. Special flavor substances were formed after yeast extract and RF treatment. Yeast extract and RF promoted water state transition to more immobilized water. Yeast extract and RF induced the uniform distribution of water, microstructure and Na + . Abstract: This study investigated the potential of yeast extract and radio frequency (RF) treatment as a strategy of reducing salt and enhancing saltiness perception for Lentinus edodes bud. The results of E-nose demonstrated yeast extract and RF treatment improved the saltiness of Lentinus edodes bud. Meanwhile, yeast extract and RF treatment significantly decreased the addition of salt ( P  < 0.05), and led to the formation of special flavor substances, whereas amino acid nitrogen content decreased. On the other hand, sensory attribute, hardness, total flavonoid and phenolic content, antioxidant capacity of L. edodes buds significantly ( P  < 0.05) increased after the yeast extract combined with RF treatment. In addition, the modification of water distribution, the formation of dense structure, uniform microstructure and Na + distribution were observed in treated sample, causing the enhancement of saltiness perception. Accordingly, the alteration of properties contributed to higher sensory properties of texture, taste, flavor, and overall acceptability.